The Key Challenges of Implementing E-Learning in Engineering Training Programs - Yahaya, S. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Developing an effective e-learning program is a great challenge since there are several tools, technologies and approaches to be considered. Industry pioneers mainly agree that e-learning will continue to become a driving force in the business sector; but apart from the many issues in designing and developing such a program, the industry is also faced with the challenges in overcoming other problems which will be discussed in this article.